Veil of shadows ebook - Hunter, Erin (Warriors: The Broken Code, 2020)
The #1 nationally bestselling Warriors series continues! Discover more epic adventures in the third book in the action-packed Broken Code story arc. After losing one of his nine lives, ThunderClan's leader, Bramblestar, became intent on rooting out and exiling cats he claims are traitors to the warrior code. But some cats know the truth: this isn't the real Bramblestar, and their leader's true spirit is desperate to return to its rightful place before the rising tension among the five Clans erupts into outright war. Packed with action and intrigue, this sixth Warriors series is the perfect introduction for readers new to the Warriors world, while dedicated fans will be thrilled to discover the new adventures that unfold after the events of A Vision of Shadows.